The effect of social media activities on brand loyalty for banks: The role of brand trust - Sulaiman Althuwaini (Administrative Sciences, 2022)
The aim of this research was to examine the impact of social media marketing activities on brand trust and brand loyalty in the banking sector. Based on an online survey of 252 users who follow banking services suppliers on social media located in Saudi Arabia, data were gleaned and analyzed via Smart-PLS (3.0). The findings showed that social media marketing activities, namely customization, entertainment, and promotions, were reported to have the highest impact on trust and loyalty. This study emphasizes the role of trust as mediating brand loyalty in social media marketing. The implications for marketing managerial and future research are discussed.
Keywords: 350; brand loyalty; brand trust; social media marketing